Black pleural effusion due to pancreatic pseudocyst: A case report. Issue 50 (December 2017) - Guo, Feng; Wu, Junli; Peng, Yunpeng; Tu, Min; Xiao, Bin; Dai, Cuncai; Jiang, Kuirong; Gao, Wentao; Li, Qiang; Wei, Jishu; Chen, Jianmin; Xi, Chunhua; et al.
Abstract: Rationale: Black pleural effusion (BPE) is an extremely uncommon type of pleural fluid, which can be due to infection, primary or metastatic malignancy, and hemorrhage. As reported in previous studies, BPE is also observed in some patients with pancreatic pseudocyst. Patient concerns: We herein reported a case of a 14-year-old female patient who was admitted to our center with a history of cough for 1 and a half months and right chest pain for 1 month. Before this, she was consecutively hospitalized in 3 different hospitals due to the same symptoms. However, the previous treatments were ineffective due to the lack of a definitive diagnosis. Laboratory examination of the pleural effusion showed BPE with a high amylase concentration. Chest x-ray and computed tomography (CT) showed massive pleural effusion, more prominent in the right chest. CT and MRCP of the abdomen showed a cystic lesion located in the tail of the pancreas, which entered the chest cavity via an esophageal hiatal hernia. Diagnoses: pancreatic pseudocyst. Interventions: After confirming that the tumor was a pancreatic pseudocyst by intraoperative biopsy, internal drainage to the jejunum was performed. Outcomes: The postoperative recovery was rapid and without complications, and the final discharge diagnosis was idiopathic pancreatic pseudocyst (without history of pancreatitis or pancreatic injuries) with BPE of the right chest. Lessons: This case demonstrates that massive BPE could present as a rare complication of pancreatic pseudocyst, and surgery is a potential treatment for such patients.